(untitled) (Journal of Parents and Teachers, 2014)
With LOE (Ley órganica de Educación) it comes the concept of Basic competency that is what a student must achieve before getting into the labour market. It is the capacity of calling up knowledge, skills and attitudes to take decisions to solve effectively some problems or situations in life. Therefore, being competent means knowing how to choose what is useful to face new situations. At schools it means a change in teaching and learning processes.